Design Based on Multicultural Values in Pondok Modern Darussalam Gontor - Syarifah, Syarifah; Maskuri, Maskuri; Mistar, Junaidi; Hosna, Rofiatul (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This research investigates the implementation of multicultural Islamic values in Pondok Modern Darussalam Gontor, a renowned Islamic educational institution in Indonesia. The primary objective of this study is to comprehend how Islamic Religious Education (PAI) values encompassing tolerance, cultural diversity, and interfaith dialogue are applied in the multicultural context of this Islamic boarding school. The research methodology employed is a qualitative approach with semi-structured interviews and participatory observation as the primary data collection instruments. The research subjects encompass teachers, students, and administrators at Pondok Modern Darussalam Gontor. Qualitative data obtained from interviews and observations are analyzed using content analysis. The findings reveal various practices and efforts undertaken by the institution in implementing multicultural PAI values. Additionally, the study identifies challenges and opportunities encountered in the process of implementing these values. This research holds significant implications for a deeper understanding of Islamic religious education in a multicultural context and can offer guidance to similar educational institutions in realizing inclusive and tolerant religious education in an increasingly diverse world." With a comment about the importance of the results or conclusions brief.